A four-channel ICCD framing camera with nanosecond temporal resolution and high spatial resolution. Issue 13 (29th July 2021) - Fang, Yuman; Zhang, Minrui; Wang, Junfeng; Guo, Lehui; Liu, Xueling; Lu, Yu; Tian, Jinshou
Abstract : In this paper, a high spatial resolution, high gating speed framing camera capable of four separate two-dimensional images is designed and tested. A mirror-based image splitter has been designed and developed to provide a separate image for each arm with equal path length and equal intensity splitting while having a spectral flat response. Fast gating of a single frame is accomplished by using a proximity-focused microchannle-plate image-intensifier (MCPII) gated by a MOSFET-based pulse module with adjustable gate width from 3 ns to D.C. operation. Multiple frames are obtained by using multiple gated tubes with time intervals between consecutive frames can be adjusted flexibly. Its spatial resolution reaches 36.5 lp/mm with each frame having a 4.6-ns gate width. Furthermore, a three-dimensional MCPII model is developed to investigate the transit time and spatial resolution of the proximity-focused MCPII based on the Finite Integral Technique (FIT) and Monte Carlo method (M–C method).